2022
DOI: 10.1111/jfd.13663
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the pancreas as a prime target for histopathological diagnosis of Tilapia parvovirus (TiPV) infection in Nile tilapia, Oreochromis niloticus

Abstract: Tilapia parvovirus (TiPV) is an emerging virus reportedly associated with disease and mortality in farmed tilapia. Although previous descriptions of histopathological changes are available, the lesions reported in these are not pathognomonic. Here, we report Cowdry type A inclusion bodies (CAIB) in the pancreas as a diagnostic histopathological feature found in adult Nile tilapia naturally infected with TiPV. This type of inclusion body has been well-known as a histopathological landmark for the diagnosis of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
4
5
0
Order By: Relevance
“…The presence of TiPV in the egg of infected tilapia indicates the possibility of vertical transmission. Our observation corroborates the ndings of Dong et al [17] who reported the presence of TiPV in oocyte membranes and the capability of TiPV for vertical transmission. Histopathological examination revealed the lesions characterized by lymphocytic in ltration in all vital organs of infected sh as observed by Liu et al [6].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The presence of TiPV in the egg of infected tilapia indicates the possibility of vertical transmission. Our observation corroborates the ndings of Dong et al [17] who reported the presence of TiPV in oocyte membranes and the capability of TiPV for vertical transmission. Histopathological examination revealed the lesions characterized by lymphocytic in ltration in all vital organs of infected sh as observed by Liu et al [6].…”
Section: Discussionsupporting
confidence: 93%
“…The viral infection has been con rmed by the appearance of the typical CPE of forming CAIB in the nucleus of infected cells and PCR. The CAIB observed in the infected cells of SHK and SPF was similar to the CAIB observed by Dong et al [17] in the pancreatic cells of TiPV infected tilapia. Dong et al [17] detected the CAIB in the pancreatic cells only but not in other infected tissues of tilapia and suggested the use of pancreas for histopathological diagnosis of TiPV infection.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Since TiPV is an emerging pathogen, until now, only molecular methods and virus isolation have been available for the detection of TiPV (Dong et al, 2022;Liu et al, 2020;Piewbang et al, 2022;Yamkasem et al, 2021), and techniques that offer rapid results with ready implementation for on-farm screening have not yet been developed. Although conventional and quantitative PCR assays have been developed and applied to identify TiPV in fish samples, these PCR methods require skilled technicians, expensive equipment, and sophisticated laboratories, which limits their application for disease screening at a farm level.…”
Section: Introductionmentioning
confidence: 99%